Achilles'heel of laparoscopic pancreatectomy: reconstruction of the remnant pancreas. (2nd July 2020) - Wu, Jiacheng; Zhang, Guofeng; Yao, Xiaoxiao; Xiang, Yien; Lin, Ruixin; Yang, Yongsheng; Zhang, Xuewen
ABSTRACT: Introduction: Laparoscopic pancreatic reconstruction is a challenging procedure and is considered the Achilles' heel of laparoscopic pancreatectomy. Multiple techniques of laparoscopic pancreatic reconstruction have been reported, but the optimal technique remains unclear. Areas covered: This paper provides a brief introduction to the developmental status and major related complications of laparoscopic pancreatic reconstruction. We reviewed all published literature on the technology of laparoscopic pancreatic reconstruction within the last 5 years and herein discuss the advantages and disadvantages of different reconstruction methods. We also discuss several details of different reconstruction techniques in terms of their significance to the operation and complications. Expert opinion: No individual method of laparoscopic pancreatic reconstruction is considered optimal for all conditions. The reconstruction strategy should be based on the surgeon's proficiency with laparoscopic technology and the patient's individual risk factors. Personalized methods of pancreatic reconstruction may more effectively reduce morbidity and mortality.